Differential Antioxidant Compounds and Activities in Seedlings of Two Rice Cultivars Under Chilling Treatment - Du, Shangguang; Huang, Xueyong; Cai, Yali; Hao, Yingbin; Qiu, Shengrong; Liu, Lihua; Cui, Meng; Luo, Liping (Frontiers in Plant Science, 2021)
Variations in antioxidant compounds were examined in seedlings of two rice cultivars (Qiutianxiaoting and 93-11) exposed to low temperature (4℃) for 0 h, 12 h, 36 h, and 48 h. Antioxidant activity was identified by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. The concentrations of total phenols, flavonoids, chlorophyll, and anthocyanins were determined by spectrophotometry. In addition, high-performance liquid chromatography (HPLC) was used to reveal the changes in phenolic compound concentrations in rice seedlings under chilling treatment. Results showed that antioxidant concentrations and antioxidant activity after chilling treatment were higher in 93-11 compared to Qiutianxiaoting, reaching the highest level at 36 h chilling treatment in 93-11. Phenolic compounds in Qiutianxiaoting decreased between 12 h and 36 h but then increased at 48 h, whereas the corresponding levels in 93-11 increased as chilling time increased. Moreover, ten phenolic compounds were detected and quantified by HPLC, of which gallic acid and caffeic acid tended to only exist in 93-11, whereas rutin was observed only in Qiutianxiaoting. The results of this study could be leveraged to optimize the antioxidant potential of rice in the context of healthy food choices.